Desain Reartikulasi Kampung To-Kaili di Kabupaten Sigi - ikram, Ikram; Mulyati, Ahda (JURNAL RUANG / ISSN : 2085-6962, 2025)
The Kaili tribe is one of the largest ethnic groups in the Central Sulawesi region, particularly in Donggala Regency, Sigi Regency, Kulawi and Mount Raranggonau. The Kaili tribe is also found in the east coast region, Parigi-Moutong, Tojo Una-una Regency and Poso Regency. According to history, the Kaili people in Central Sulawesi first settled around the river. The village (Ngata) in Sigi regency, Bora Village, Biromaru District, is one of the Kaili villages that can still be found today. However, the condition of the traditional buildings in the area is currently in an unmaintained and almost damaged physical condition. Therefore, the purpose of this research is to create a To-Kaili village rearticulation design that represents the diversity of traditional Kaili architecture. The research method used is the design method with descriptive data collection techniques, namely describing the To-Kaili Village in writing and being able to produce a To-Kaili Village design in Sigi Regency. The result of this research is the recommendation of "Rearticulation Design of To-Kaili Village in Sigi Regency" from the aspects of (1) the design function of Kaili Village, (2) the potential development of Kaili Village, (3) the existing conditions of research, (4) the design approach, and (5) the concept of cosmology in inhabited space.